2008
DOI: 10.1111/j.1365-2095.2007.00529.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary probiotic supplementation in growth and health of live-bearing ornamental fishes

Abstract: Bacillus subtilis, a probiont isolated from the intestine of Cirrhinus mrigala (Hamilton), was incorporated in fish feed at four different concentrations (5 · 10 8 , 5 · 10 7 , 5 · 10 6 and 5 · 10 5 cells g )1 ) and fed to Poecilia reticulata (Peters), Poecilia sphenops (Valenciennes), Xiphophorus helleri (Heckel) and Xiphophorus maculatus (Gunther) for a period of 90 days. The growth parameters, proximate composition of whole body, digestive enzymes and gut microbiology were monitored at regular monthly inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
71
2
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(88 citation statements)
references
References 32 publications
(37 reference statements)
11
71
2
4
Order By: Relevance
“…According to the results obtained in the growth of fish fed with the probiotic bacteria isolated in this study, we observed that the use of food fish was higher in treatments in which they contain added probiotic strains, especially with Bs3 strain in which the fish were much higher growth in total length, weight and width (with almost 50% increase compared to the control group and the combination of probiotic strains). These results agree with the study by Ghosh et al, (2008), which reported significant differences in the growth of ornamental fish species Poecilia reticulata, Poecilia sphenops, Xiphophorus maculatus and Xiphophorus hellieri, after being fed with feed enriched Bacillus sp for a period of 60 days, compared with a control treatment without probiotic.…”
Section: Discussionsupporting
confidence: 82%
“…According to the results obtained in the growth of fish fed with the probiotic bacteria isolated in this study, we observed that the use of food fish was higher in treatments in which they contain added probiotic strains, especially with Bs3 strain in which the fish were much higher growth in total length, weight and width (with almost 50% increase compared to the control group and the combination of probiotic strains). These results agree with the study by Ghosh et al, (2008), which reported significant differences in the growth of ornamental fish species Poecilia reticulata, Poecilia sphenops, Xiphophorus maculatus and Xiphophorus hellieri, after being fed with feed enriched Bacillus sp for a period of 60 days, compared with a control treatment without probiotic.…”
Section: Discussionsupporting
confidence: 82%
“…containing probiotics in common carp [46]. B. subtilis in four livebearing ornamental fishes [47]. Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of using probiotics in fish aquaculture were recently reviewed by Nayak [19] and Qi et al [20]. The main beneficial effects of probiotic use in fish aquaculture are growth performance improvement [21,22] and disease control through immunity enhancement [19,20,23] and pathogens exclusion [20]. The bacteria could also have improved digestive activity via synthesis of vitamins and cofactors or via enzymatic improvement [4].…”
Section: Discussionmentioning
confidence: 99%